Influence of elastic strains on LPE growth kinetics in the Cd-Hg-Te System - Moskvin, P.P.; Rashkovetsky, L.V.; Khodakovsky, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
By comparing the results of calculations concerning the dependence of the
parameters of a layer on the growth conditions with and without regard for mechanical
strains in the growing system, we have analyzed the influence of the elastic energy of the
strained solid phase on the phase formation in the Cd–Hg–Te system. It is shown that the
occurrence of elastic strains in a layer results in an insignificant reduction of the growth
rate and has almost no influence on the composition of a growing layer. The ideas of
coherently matched phases in the presence of elastic deformations in the system, as well
as the assumption about the existence of the chemical equilibrium of phases on the interface,
give rather close results as for the crystallization of the material. Both approaches
describe the experimental data on the growth of layers in various temperature-time
regimes quite satisfactorily